Linking Gamification Technology, Motivation, and Flow to Student Engagement and Problem-Solving in Education - Dedy Irfan; Didik Hariyanto; Heri Prabowo; Zulhendra Zulhendra; Edidas Edidas; Andhika Herayono (Journal of Applied Engineering and Technological Science (JAETS), 2026)
The use of gamification in higher education has been widely explored as a strategy to enhance student engagement and learning outcomes. However, many empirical studies on gamified learning primarily examine direct relationships between gamification and motivational outcomes, while the underlying experiential mechanisms that connect gamification with sustained engagement and higher-order cognitive performance remain insufficiently understood. In particular, few structural modeling studies simultaneously examine the roles of motivation, flow, and presence within a unified experiential framework. This study investigates how gamification technology influences student engagement and problem-solving competence through the experiential mechanisms of motivation, flow, and presence. A quantitative research design was employed involving 100 undergraduate students enrolled in technology-oriented programs (electronics engineering education and informatics engineering education) at Universitas Negeri Padang. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the proposed mediation pathways. The results indicate that gamification technology significantly influences motivation (β = 0.412, p < 0.001), flow (β = 0.508, p < 0.001), and presence (β = 0.436, p < 0.001). Among the experiential constructs, flow shows the strongest influence on student engagement (β = 0.483, p < 0.001), while the effect of motivation on engagement is not statistically significant (β = 0.097, p = 0.18). Student engagement subsequently demonstrates a significant effect on problem-solving competence (β = 0.498, p < 0.001). The structural model explains 30.6% of the variance in student engagement and 24.8% of the variance in problem-solving competence. These findings suggest that immersive experiential states, particularly flow, play an important role in shaping engagement in gamified learning environments. The study contributes to the gamification literature by proposing and empirically testing an experiential pathway model that integrates psychological immersion mechanisms with behavioral learning outcomes in technology-enhanced education.